Integrating traditional ecological knowledge into US public land management: Knowledge gaps and research priorities - Souther, Sara; Colombo, Sarah; Lyndon, Nanebah N. (Frontiers in Ecology and Evolution, 2023)
Traditional Ecological Knowledge (TEK) is an understanding of natural systems acquired through long-term human interactions with particular landscapes. Traditional knowledge systems complement western scientific disciplines by providing a holistic assessment of ecosystem dynamics and extending the time horizon of ecological observations. Integration of TEK into land management is a key priority of numerous groups, including the United Nations and US public land management agencies; however, TEK principles have rarely been enshrined in national-level US policy or planning. We review over 20 years of TEK literature to describe key applications of TEK to ecological understanding, conservation, restoration and land management generally. By identifying knowledge gaps, we highlight research avenues to support the integration TEK into US public land management, in order to enhance conservation approaches and participation of historically underrepresented groups, particularly American Indian Tribes, in the stewardship of ancestral lands critical to practice living cultural traditions.